2019
DOI: 10.1002/bit.26905
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the yeast metabolic model to include iron metabolism and its use to estimate global levels of iron‐recruiting enzyme abundance from cofactor requirements

Abstract: Metabolic networks adapt to changes in their environment by modulating the activity of their enzymes and transporters; often by changing their abundance. Understanding such quantitative changes can shed light onto how metabolic adaptation works, or how it can fail and lead to a metabolically dysfunctional state. We propose a strategy to quantify metabolic protein requirements for cofactor‐utilising enzymes and transporters through constraint‐based modelling. The first eukaryotic genome‐scale metabolic model to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
(88 reference statements)
0
9
1
Order By: Relevance
“…In order to benchmark our findings, we also investigated the response of yeast cells to the loss of a copy of YFH1 , encoding the yeast frataxin homolog, which has a very similar function to ARH1 in iron-sulphur cluster assembly, and also of ATM1 , encoding the ABC transporter that exports mitochondrially synthesized precursors of iron-sulphur clusters to the cytosol. Our results showed that neither a YFH1/yfh1Δ nor an ATM1/atm1Δ hemizygote showed any significant difference form their cognate homozygous wild types in their metabolic or phenotypic responses 21 .…”
Section: Introductioncontrasting
confidence: 59%
“…In order to benchmark our findings, we also investigated the response of yeast cells to the loss of a copy of YFH1 , encoding the yeast frataxin homolog, which has a very similar function to ARH1 in iron-sulphur cluster assembly, and also of ATM1 , encoding the ABC transporter that exports mitochondrially synthesized precursors of iron-sulphur clusters to the cytosol. Our results showed that neither a YFH1/yfh1Δ nor an ATM1/atm1Δ hemizygote showed any significant difference form their cognate homozygous wild types in their metabolic or phenotypic responses 21 .…”
Section: Introductioncontrasting
confidence: 59%
“…The budding yeast S. cerevisiae has been used as a model organism to study many aspects of iron homeostasis and regulation in eukaryotes. In fact, recent systems biology approaches have proposed a comprehensive mechanistic model for iron metabolism that has also been integrated into a whole-yeast metabolic model (Dikicioglu and Oliver, 2019;Lindahl, 2019). Here, we briefly review the mechanisms that control the adaptation of S. cerevisiae to changes in iron bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Yeast 1 has been upgraded to the latest version, Yeast 7, in the past few years by incorporating new biological information and by correcting critical modeling errors, such as the removal of thermodynamically infeasible reactions [5356]. Very recently, Yeast 7.Fe [57] was extended from Yeast 7.6 [56] by including additional information on iron metabolism, which had not been properly considered in the previous GEMs. The Yeast 7.Fe now allows estimation of the optimal turnover rate of iron cofactors and more rigorous examination of metabolism.…”
Section: Current Status Of Reconstructed Genome-scale Metabolic Modelsmentioning
confidence: 99%